2022
DOI: 10.1093/mnras/stac113
|View full text |Cite
|
Sign up to set email alerts
|

BEBOP II: sensitivity to sub-Saturn circumbinary planets using radial-velocities

Abstract: BEBOP is a radial-velocity survey that monitors a sample of single-lined eclipsing binaries, in search of circumbinary planets by using high-resolution spectrographs. Here, we describe and test the methods we use to identify planetary signals within the BEBOP data, and establish how we quantify our sensitivity to circumbinary planets by producing detection limits. This process is made easier and more robust by using a diffusive nested sampler. In the process of testing our methods, we notice that contrary to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…The inclusion of this signal improves the BIC by just over 2, the threshold for positive evidence (Raftery 1995). This BIC improvement corresponds to a ∼ 2-sigma detection, hence our current tentative stance on the planetary nature of this signal (see Table 2 in Standing et al (2022), where Δ BIC = 2 is equivalent to a Bayes Factor = 3). The log likelihood improves by ∼ 10, meaning this statistic shows significant evidence that this signal is present in the data (with the threshold for strong evidence being Δ lnL > 7, Kass & Raftery 1995).…”
Section: An Additional Interior S-type Planet?mentioning
confidence: 70%
See 2 more Smart Citations
“…The inclusion of this signal improves the BIC by just over 2, the threshold for positive evidence (Raftery 1995). This BIC improvement corresponds to a ∼ 2-sigma detection, hence our current tentative stance on the planetary nature of this signal (see Table 2 in Standing et al (2022), where Δ BIC = 2 is equivalent to a Bayes Factor = 3). The log likelihood improves by ∼ 10, meaning this statistic shows significant evidence that this signal is present in the data (with the threshold for strong evidence being Δ lnL > 7, Kass & Raftery 1995).…”
Section: An Additional Interior S-type Planet?mentioning
confidence: 70%
“…In this case there is no need for complex deconvolution to recover individual spectra. It is possible to obtain very precise radial velocities on such single-lined binaries, as demonstrated by Standing et al (2022) and Triaud et al (2022). These studies focus on binary signal subtraction to detect circumbinary (Ptype) planets orbiting outside the inner stellar pair, and are able to reach a residual root mean squared scatter of 3 m s −1 (Standing et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that spectroscopically the secondary star is essentially invisible, making it a single-lined spectroscopic binary (SB1). The advantage of an SB1 is that we may achieve a radial velocity precision comparable to that around single stars of a similar brightness (∼ 1 − 2 m/s), as demonstrated in the BEBOP (Binaries Escorted By Orbiting Planets) survey for circumbinary planets (Martin et al 2019;Standing et al 2022;Triaud et al 2022).…”
Section: Introductionmentioning
confidence: 94%
“…Such terrestrial circumbinary planets (CBPs) have yet to be observed, however. While this may be attributed to observational bias against such small planets in a circumbinary orbit (Windemuth et al 2019;Martin & Fabrycky 2021;Standing et al 2022), it may also indicate that terrestrial planets do not form through core accretion in a circumbinary disk or that current core accretion models are missing key physics.…”
Section: Introductionmentioning
confidence: 99%